Trinta anos depois: para além do sítio de Castelo Velho de Freixo de Numão. Recintos murados e deposições da pré-história recente - Lopes, Susana Soares (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2020)
This article describes the study and musealization of a late prehistoric walled enclosure located at the Portuguese Upper Douro: Castelo Velho de Freixo de Numão. From the excavation started in 1989, to the opening of the site in 2007, and the publishing of a global interpretative perspective in 2019, there have been thirty years of numerous archaeological actions. I aim to summarize those actions discussing their nature and diversity. The main discovery in Castelo Velho was the identification of deposition contexts, assembling disparate materialities under different formal grammars. Such contexts date from the 3rd millennium, disappearing during the first half of the 2nd millennium BC. Deposition contexts, in association with other features, namely several narrow passages in the enclosure (probably used in successive opening and closing cycles) allowed interpreting the enclosure as a conditioned space hosting ceremonial practices during the 3rd millennium BC. Over this period, weren’t observed architectural and/or contextual discontinuities, suggesting that the site was occupied in the light of the same social dynamics. The main architectural elements of the enclosure remained active until the middle of the 2nd millennium BC. However, the traces of the occupations during this period are sparse and globally different from those of the 3rd millennium BC. Overall, the site was transformed into another place: an enclosed area, accessed only through a passage, connected to the Cogeces cultural world. The 2nd millennium BC enclosure was then a place with other social functions, whose cultural uniqueness still eludes us. Within the several questions to be made in the investigation of Castelo Velho, it should be stand out this one: What may have been the cause(s) of the turning point that took place between the end of the 3rd and the beginning of the 2nd millennium BC? We shall also ask: Has this change occurred at a regional level, does it mirror a social transformation of the Chalcolithic communities in the Upper Douro region?